The Easter egg - Brett, Jan, 1949- (New York, N.Y., U.S.A. : G.P. Putnam's Sons, 2010)
Hoppi the bunny wants to win the egg-decorating contest so the Easter Bunny will choose him to help distribute Easter eggs, but instead, while everyone else is working on their decorations, he finds himself guarding an egg that has fallen from a robin's nest.
Keywords: Eggs -- Pictorial works -- Juvenile fiction; Easter eggs -- Pictorial works -- Juvenile fiction; Contests -- Pictorial works -- Juvenile fiction; Rabbits -- Pictorial works -- Juvenile fiction